پاراستنی منداڵان لە توندوتیژی لە بەڵگەنامە یاساییە نێودەوڵەتییەكاندا توێژینەوەیەکی شیکارییە - Abdulkarim, Nigar Taher; Darwesh, Dr. Dilpak Tahir (Journal of Legal and Political Studies, 2025)
This research, entitled "Protecting Childrens from Violence in International Legal Documents," is considered one of the most important topics discussed by international organizations and documents these days. There is no doubt that children, due to their physical and intellectual capabilities, limited life experience, and limited knowledge of their rights, are vulnerable to violations of their rights through violence perpetrated against them in their normal and abnormal lives. The fundamental problem of this research is to answer the question: How does international law address violations against children? What are the responsibilities and obligations of states to reduce violence against children? From this perspective, the objective of this research is to discuss the fundamental rights guaranteed to children under international law. To achieve this objective, the research focuses on the rules for protecting children within the framework of relevant documents and agreements. At the end of the research, we presented a set of results and recommendations as a scientific effort to reduce the practice of violence against them. Keywords: Children's rights, violence, international documents, convention on the rights of the child.
Keywords: Keywords Childrens rights; violence; international documents; convention on the rights of the child